Groundbreaking but not a Universal Solution: Renewable Energy in Irrigation - Ringler, Claudia; Akbar, Zain Muhammad (2023)
Solar pumps instead of fossil fuels improve access to irrigation in remote rural areas. But they are also a temptation to consume more groundwater.